Two new peruvian species of Lepanthes (Orchidaceae) with a unique column morphology - Larsen, Bruno; Guerrero, Marcos Salas; Dignum, Johannes H. M. (Phytotaxa, 2018)
The genus Lepanthes Swartz (1799a: 85) with more than 1200 species (Bogarín et al. 2018) is the largest genus in Pleurothallidinae, comparable only with Stelis Swartz (1799b: 239). It is distributed throughout the Neotropics from central Mexico and the Antilles south to Peru and Bolivia, with only few species occurring in Brazil (Luer & Thoerle 2012). The diversity of Lepanthes species in Peru is probably underestimated. About 58–64 species have been formally recorded (Tropicos 2016, Govaerts et al. 2016, Damian & Larsen 2017), which is relatively fewer compared to neighbouring countries where the genus is relatively well known, such as Colombia and Ecuador, each with more than 300 species (Thoerle & Hirtz, 2015). At the moment, several new species and new records of the genus for the country are awaiting publication, and as more extensive exploration continues, the number of Lepanthes attributed to Peru is expected to increase.